Methodological issues of assessing the risk of a second cancer occurring in the same site as a first cancer using registry data. (December 2017) - Jégu, Jérémie; Moitry, Marie; Bara, Simona; Trétarre, Brigitte; Guizard, Anne-Valérie; Woronoff, Anne-Sophie; Daubisse-Marliac, Laetitia; Bouvier, Véronique; Troussard, Xavier; Colonna, Marc; Klein, Delphine; Lapôtre-Ledoux, Bénédicte; et al.
Highlights: Population-based studies about second primary cancer (SPC) incidence are common. Inclusion of SPC of the same site can impact Standardized Incidence Ratios (SIRs). SIRs decreased for prostate cancer and increased for cancers of paired organs. Analyses should be done for discordant sites of first and second cancer. Data collection about contralateral SPCs of paired organs could be improved. Abstract: Objective: To present methodological issues that can arise with the assessment of the risk of a second primary cancer (SPC) occurring in the same site as a first cancer using registry data. Material and methods: Data from ten French cancer registries were used, including data for patients with a first prostate cancer (in males), breast cancer (in females), and colon, lung and kidney cancer (in both sexes) diagnosed between 1989 and 2004. Standardized incidence ratios (SIRs) of SPC were computed by excluding, or not, the risk of an SPC at the same site. Results: For prostate cancer, the SIR dropped from 1.11 to 0.72 when the risk of SPC of the prostate was included. SIRs increased from 1.36 to 1.45, from 1.14 to 1.21, from 1.57 to 2.01, and from 1.37 to 1.51 for breast, colon, lung, and kidney respectively. Conclusion: The inclusion, or not, of an SPC at the same site can impact on SPC risk estimates.